KOMPETENSI KEWIRAUSAHAN, INOVASI PRODUK DAN KINERJA UMKM TERHADAP KEBERLANJUTAN UMKM DI KOTA WAINGAPU - Ranjamandi, Samuel Lu; Situmorang, Tumpal P. (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
Entrepreneurial competence, product innovation, MSME performance, and MSME sustainability are four important factors needed by Micro, Small, and Medium Enterprises (MSMEs) to face environmental challenges in a dynamic business world and achieve high business performance. This study aims to examine the influence of entrepreneurial competence, product innovation, MSME performance, and MSME sustainability. This research was conducted on MSMEs in Waingapu City. The sample in the study was 100 MSMEs determined through the purposive sampling method. Data was collected through a survey with questionnaire distribution. The data analysis technique uses a structural equation model with the Partial Least Square (PLS) approach. The results of the study show that entrepreneurial competence does not have a significant positive effect on the performance of MSMEs, but product innovation has a significant effect on the performance of MSMEs and the performance of MSMEs has a significant positive effect on the sustainability of MSMEs. The results of this study indicate that entrepreneurial competence, product innovation, and MSME performance towards the sustainability of MSMEs are accepted.